Psychopathy and Machiavellianism: A Distinction Without a Difference?. Issue 4 (6th April 2016) - Miller, Joshua D.; Hyatt, Courtland S.; Maples‐Keller, Jessica L.; Carter, Nathan T.; Lynam, Donald R.
Abstract: A robust literature has emerged on the Dark Triad (DT) of personality—Machiavellianism (MACH), psychopathy, and narcissism. Questions remain as to whether MACH and psychopathy are distinguishable and whether MACH's empirical and theoretical networks are consistent. In Study 1 ( N  = 393; MTurk research participants), factor analyses were used to compare two‐factor (MACH and psychopathy combined + narcissism) and three‐factor models, with both fitting the data equally well. In Studies 1 and 2 ( N  = 341; undergraduate research participants), DT scores were examined in relation to a variety of external criteria, including self‐ and informant ratings of personality, adverse developmental experiences, and psychopathological symptoms/behaviors. In both studies, MACH and psychopathy manifested nearly identical empirical profiles and both were significantly related to disinhibitory traits thought to be antithetical to MACH. In Study 3 ( N  = 36; expert raters), expert ratings of the Five‐Factor Model traits prototypical of MACH were collected and compared with empirically derived profiles. Measures of MACH yielded profiles that were inconsistent with the prototypical expert‐rated profile due to their positive relations with a broad spectrum of impulsivity‐related traits. Ultimately, measures of psychopathy and MACH appear to be measuring the same construct, and MACH assessments fail to capture the construct as articulated in theoretical descriptions.